Professional characteristics of an educator: A survey of literature - Anitha, J.; Krishnaveni, R. (Journal of Management and Development Studies, 2013)
Literature has shown that various studies have dealt with different professional features of teaching and they have focused on one or few professional characteristics of educators. In spite of the immense amount of literature on educator characteristics, a comprehensive study that would encompass the vital professional characteristics of an educator in total is lacking. This has instigated the researcher to take up the study to identify the professional characteristics of an educator. An attempt was made in identifying the educators' characteristics using student outcome as a boundary criterion to select the characteristics from among several that are available in the literature. Therefore, a new model of professional characteristics of educators was proposed. This paper discusses in detail, the characteristics of a profession in general and the wide range of educator’s characteristics as studied in previous researches. The paper presents a wide scope for the models developed to be studied in depth to appreciate and investigate more about the professional characteristics identified through this review of literature. The models may also be tested empirically for further accumulation of knowledge in the field.